Trauma Of Violence In The Brief Wondrous Life Of Oscar Wao; A Psychological Analysis - Amelia Yuli Astuti; Situasi Putra Jaya Laia Situasi Putra Jaya Laia (Fakultas Sastra Universitas Ekasakti, 2026)
This reseach examines the